Evidence of Ginsburg-Landau behaviour in a microemulsion system - Shahidan Radiman, (Universiti Kebangsaan Malaysia, 1997)
The evolution of microemulsion microstructure formed from didodecyl dimethyl ammonium bromide, water and cyclohexane which started from being structureless (fiat scattering profile) to a mean-field Ginsburg-Landau behaviour is shown. The evolution gave the characteristic Lorentzian scattering profile as the system approaches phase separation.